2014
DOI: 10.9738/intsurg-d-13-00185.1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Outcomes and Complications of Totally Implantable Access Port Through the Internal Jugular Vein Versus the Subclavian Vein

Abstract: Totally implantable access ports (TIAPs) are generally used in oncology. Few studies have addressed complications associated with the insertion site. A total of 233 consecutive oncology patients were enrolled to receive TIAP inserts via internal jugular vein (IJV) or subclavian vein (SV). Data on clinicopathologic parameters and early/late complications were retrospectively collected. No differences were found early and late complication rates. Catheter injury was observed more frequently in the IJV group (2.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
4
27
1
1
Order By: Relevance
“…The USG group had more success in the first attempt of puncture when compared to the other two groups and less technique failure when compared to the IJB group. These results are similar to those obtained by Granziera et al and Nagasawa et al .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The USG group had more success in the first attempt of puncture when compared to the other two groups and less technique failure when compared to the IJB group. These results are similar to those obtained by Granziera et al and Nagasawa et al .…”
Section: Discussionsupporting
confidence: 93%
“…The USG group had more success in the first attempt of puncture when compared to the other two groups and less technique failure when compared to the IJB group. These results are similar to those obtained by Granziera et al and Nagasawa et al [4,19]. We believe that higher success rate in first attempt and lower technique failure contribute to reduce the procedure duration, the risk of more serious complications and improve the patient's perception toward the procedure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is reported that placing a TIVAP catheter in the internal jugular vein has fewer complications than placing it in the subclavian vein 3. However, other studies have reported no difference in the frequency of complications between placing a TIVAP catheter in the internal jugular vein and that in the subclavian vein 4. In this case, fracture of the TIVAP catheter occurred in the subclavian area.…”
Section: Discussionmentioning
confidence: 64%
“…An immediate complication was defined as an event occurring within 7 days after implantation. 17,18 Statistical analysis Demographic data were described by crude value and representative percentage. Categorical data were stratified by various factors and compared by chi-square test, while continuous data were compared with t-test.…”
Section: Data Collectionmentioning
confidence: 99%